Chinese Multinational Enterprises: Effects on World Poverty (2021)
This paper aimed to determine the effect of the Chinese multinational enterprises in the reduction of poverty in a group of 36 high and upper-middle-income countries where they operate for the period 2009-2018. A dynamic panel data econometric methodology was used. It is found that these multinationals positively influence poverty reduction. Consequently, they can be considered as a central mechanism of the global dynamics of poverty. The document contributes to the limited literature that quantitatively analyses the role of Chinese multinationals in reducing poverty.